Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Sub-cycle control of multi-THz high-harmonic generation and all-coherent charge transport in bulk semiconductors - Lange, C.; Schubert, O.; Hohenleutner, M.; Langer, F.; Baierl, S.; Maag, T.; Urbanek, B.; Edwards, E. R. J.; Woltersdorf, G.; Bougeard, D.; Huttner, U.; Golde, D.; et al. (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIV)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (SPIE Proceedings Vol. 9361: Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Time-domain calculations of shift currents in bulk GaAs - Podzimski, Reinold; Duc, Huynh T.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XIX)

Michael Fischer: Religion, Nation, Krieg. Der Lutherchoral EIN FESTE BURG IST UNSER GOTT zwischen Befreiungskriegen und Erstem Weltkrieg, Münster/New York 2014 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Kein feste Burg! Vor 100 Jahren lässt Claude Debussy den Lutherchoral erklingen - Schroeter-Wittke, Harald (Praktische Theologie)

Frömmigkeit und Blasphemie - das geht zu z/weit. - Schroeter-Wittke, Harald (Text-Raum)

Verwirrte Hirten. Talking Horns und St.Ankowski - Schroeter-Wittke, Harald (Praktische Theologie)

Migration und Gender. Medienaneignung in der frühen Bildung in intersektionaler Perspektive - Goetz, Ilka; Günesli, Habib; Marci-Boehncke, Gudrun (Medien + Erziehung)
Dieser Beitrag thematisiert die Perspektive verknüpfter Merkmale in der Wahrnehmung von Kindern im (medialen) Erziehungsprozess durch Eltern und Erzieherinnen. Aufgefallen ist diese Merkmalsverknüpfung – auch „Intersektionalität“ (Collins 1998) – bei der Auswertung eigener empirischer Daten zur Einschätzung von Bildungserfolgen bei vier- und fünfjährigen Jungen und Mädchen mit und ohne Migrationshintergrund (vgl. hierzu Broden/Mecheril 2007) durch ihre Eltern und Erzieherinnen. Diese wird erst dann unterschiedlich, wenn Geschlecht und kultureller Hintergrund gemeinsam als Merkmale berücksichtigt werden. Pädagogisch weist dieses Ergebnis auf Sensibilisierungsbedarf hin, um Bildungsgerechtigkeit kritisch im Blick zu halten.

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Gerechtigkeit als Gegenstand erwägungsorientierten Denkens - Ein Seminarbericht - Jende, Yvonne Kristin; Dear, K.; Garnjost, F.; Höcker, Linus; Matysiak, B.; Täschner, J. (Erwägen - Wissen - Ethik)

Innovative Processing Techniques for the Manufacture of High-Performance Active Elements from Ultra High-Strength Steel Plate - Homberg, Werner; Rostek, Tim

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Fieback, K.; Morbach, A.; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
This study presents the results of an experimental investigation of the influence of latent thermal heat storage elements on the power consumption as well as the temperature distribution of commercial household refrigerators.Two evaporator types and a standard wireand- tube condenser are equipped with copolymer-bound phase change materials (PCM) and the performance is determined under standard conditions. The results show that refrigerating appliances equipped with PCM can be optimized through modifications of the control strategy to achieve different targets: (a) Power consumption can be significantly reduced by increasing the evaporator and decreasing the condenser temperature. (b) Temperature fluctuations in the refrigerator’s fresh-food compartment during the cooling cycle can be reduced from 4 °C to 0.5 °C. (c) The cooling cycle duration can be tripled without compromising the fresh-food compartment conditions. The latter may help to meet the growing demand for balancing power consumption to stabilize the power grid, e.g. if the share of highly fluctuating, sustainable energy supply is large.

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Internal Flow-Turning - An Innovative Technology for the Manufacture of Tailored Tubes - Homberg, Werner; Rostek, Tim; Wiens, Eugen (Key Engineering Materials)
In order to optimise the material utilisation and improve the lightweight design of automotive parts tailored hollow profiles are needed, especially as semi-finished parts for hydroforming. Internal Flow-Turning is an innovative incremental forming technology which enables the manufacture of tubes featuring a varying wall thickness and a constant outer diameter. These characteristics facilitate the material feed at hydroforming processes significantly. In addition, the spinning-related forming technology improves the mechanical material properties, shape and dimensional accuracy, and the surface quality of parts produced.

Vector bundles on plane cubic curves and the classical Yang-Baxter equation - Burban, Igor; Henrich, T. (Journal of the European Math. Society)

Auf der Suche nach digitalen Konzepten - Eickelmann, Birgit (Frankfurter Allgemeine Zeitung Verlagsspezial (V4) zum Tag der Bildung)

Modellierung und Messung medienpädagogischer Kompetenz - Grundlagen und erste Ergebnisse - Herzig, Bardo; Martin, A.; Schaper, N.; Ossenschmidt, D. (Kompetenzerwerb an Hochschulen: Modellierung und Messung. Zur Professionalisierung angehender Lehrerinnen und Lehrer sowie frühpädagogischer Fachkräfte.)

Lernen mit Medien in formalen und informellen Kontexten. - Herzig, Bardo; Martin, A. (Zukunft des Lernens. Neurobiologie und Neue Medien.)

Digitale Medien in der Lehr-Lernforschung. Ergebnisse und Herausforderungen aus interdisziplinärer Sicht - Herzig, Bardo (Medienvielfalt in der Deutschdidaktik. Erkenntnisse und Perspektiven für Theorie, Empirie und Praxis)

Integrative Medienbildung in der Geschichtsdidaktik am Beispiel von TwHistory-Projekten - Aßmann, S.; Herzig, Bardo (Medien machen Geschichte. Neue Anforderungen an den geschichtsdidaktischen Medienbegriff im digitalen Wandel.)

Interaction of high-order solitons with external dispersive waves - Meier, Torsten; Oreshnikov, I.; Driben, R.; Yulin, A.V. (Optics Letters)
The effect of mutual interaction between second-order soliton and dispersive waves (DWs) is investigated. It is predicted analytically and confirmed numerically that DWs (both transmitted and reflected components) become polychromatic after interaction with the soliton. Collision with DWs of considerable intensity can lead to acceleration/deceleration and central frequency shift of the soliton, while still preserving the soliton’s oscillating structure. Two second-order solitons with resonant DWs trapped between them can form an effective solitonic cavity with “flat” or “concave mirrors,” depending on the intensity of the input.

Brücken bauen in der Werkstatt: Die Bedeutung von Forschungswerkstätten in der Bearbeitung des Theorie-Praxis-Verhältnisses in der Lehrer/innenbildung - Freitag, Christine; Thünemann, S. (Brücken bauen – Praxisforschung zu Übergängen im Bildungssystem)

Gewalt und Zuchtmittel in der Schulgeschichte - Freitag, Christine (Handbuch Aggression, Gewalt und Kriminalität bei Kindern und Jugendlichen)

Anaerobic Microbial Transformation of Halogenated Aromatics and Fate Prediction Using Electron Density Modeling - Cooper, M.; Wagner, A.; Wondrousch, D.; Sonntag, F.; Sonnabend, A.; Brehm, Martin; Schüürmann, G.; Adrian, L. (Environ. Sci. Technol.)

Triphilic Ionic-Liquid Mixtures: Fluorinated and Non-Fluorinated Aprotic Ionic-Liquid Mixtures - Hollóczki, O.; Macchiagodena, M.; Weber, H.; Thomas, M.; Brehm, Martin; Stark, A.; Russina, O.; Triolo, A.; Kirchner, B. (ChemPhysChem)

Domain Analysis in Nanostructured Liquids: A Post-Molecular Dynamics Study at the Example of Ionic Liquids - Brehm, Martin; Weber, H.; Thomas, M.; Hollóczki, O.; Kirchner, B. (ChemPhysChem)

Voronoi Dipole Moments for the Simulation of Bulk Phase Vibrational Spectra - Thomas, M.; Brehm, Martin; Kirchner, B. (Phys. Chem. Chem. Phys.)

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, C.; Wang, Z.; Koke, Isabel; Tröster, Thomas

Textile composites in the automotive industry - Abel, P.; Lauter, C.; Gries, Thomas; Tröster, Thomas (Fatigue of Textile Composites)

Intrinsische Herstellung hybrider Strukturkomponenten in einem modifizierten RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Meschut, Gerson; Schaper, Mirko; Tröster, Thomas

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, Christian; Wang, Zheng; Koke, Isabel; Tröster, Thomas (20th International Conference on Composite Materials, Copenhagen)

Erlösung und Freiheit. Anmerkung zu Magnus Striet - Tatari, Muna (Streitfall Erlösung)

Erlösung, Offenbarung und Schöpfung - Soteriologie als Diskurshorizont des christlich-muslimischen Gesprächs - Ghaffar, Zishan (Streitfall Erlösung)

Jesus redivivus. Der koranische Jesus im Kontext von Prophetologie - Ghaffar, Zishan (Jesus Christus. Von alttestamentlichen Messiasvorstellungen bis zur literarischen Figur)

Tārīḫgoḏārī-ye ḥadīṯ: rawešhā wa nemūnehā - Aghaei Abrandabadi, Seyed Ali

Sklaverei und der Loskauf von Sklaven und Kriegsgefangenen im frühen Islam: Zwischen Theorie und Praxis - Nassery, Idris (Gefangenloskauf im Mittelmeerraum - Ein interreligiöser Vergleich)

Das Schura-Konzept - zwischen Realität und Mythos - Nassery, Idris (Macht, Religion, Politik- Wie viel Religion verträgt der Staat?)

Max Weber, die Scharia und Aspekte islamischer Wirtschaftsethik: Eine kritische Würdigung der Beobachtungen Max Webers - Nassery, Idris (Journal für Religionsphilosophie)

Blanke Machtinteressen - Wie der „Islamische Staat“ entstehen konnte - Nassery, Idris (Frankfurter Rundschau)

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)

Testing of pipe sections - Andreiev, Anatolii; Golovko, Oleksandr; Frolov, Iaroslav; Nürnberger, Florian; Wolf, Lars Oliver; Schaper, Mirko; Grydin, Olexandr (Materials Testing)
Abstract A device and the basic technology has been developed for tensile testing pipe sections samples (tensile testing PSS) for quantitative estimating ultimate tensile and yield stresses in ring samples (PSS samples) cut from pipes. This tensile testing device provides the opportunity for compensating frictional forces during the tensile test, and using exchangeable bearings, the device can be adapted to a wide assortment of pipes. Research has been carried out regarding the shape and size of a stress concentrator introduced into the sample. Relationships have been derived between the shape of the tensile loading curves and the characteristic forces for different types of stress concentrators. It is proposed to use PSS with stress concentrators to prevent plastic deformation in one of the supporting sections (this also allows to correlate the applied forces to one section). The concentrator should be introduced into the tube wall of the sample as a drilled hole. This method is comparatively simple with respect to established testing methods.

Fachdidaktisches Wissen - Validierungsstudien - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (Heterogenität und Diversität - Vielfalt der Voraussetzungen im naturwissenschaftlichen Unterricht. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bremen 2014)

Physikalisches Fachwissen in verschiedenen Studiengängen und Wissensstufen - Woitkowski, David; Riese, Josef; Reinhold, Peter (Heterogenität und Diversität - Vielfalt der Voraussetzungen im naturwissenschaftlichen Unterricht. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bremen 2014)

Modellierung und Messung des Professionswissens in der Lehramtsausbildung Physik - Riese, Josef; Kulgemeyer, Christoph; Zander, Simon; Borowski, Andreas; Fischer, Hans E.; Gramzow, Yvonne; Reinhold, Peter; Schecker, Horst; Tomczyszyn, Elisabeth (Kompetenzen von Studierenden: 61. Beiheft der Zeitschrift für Pädagogik)
Im Hinblick auf die Verbesserung der Lehrerbildung besteht ein hohes Interesse daran, die Struktur und Genese der Kompetenzen von Lehramtsstudierenden zu beschreiben. Die Ziele des vorgestellten Projekts liegen in der Modellierung und Messung domänenspezifischer und generischer Kompetenzen, die Lehramtsstudierende der Physik im Hochschulstudium erwerben sollen. Das Modell umfasst differenzierte Facetten des physikalischen Fachwissens und des physikdidaktischen Wissens sowie das fachspezifische Erklärungswissen in unterrichtsnahen Vermittlungssituationen. Es enthält zudem Annahmen über Zusammenhänge dieser Bereiche des Professionswissens. Ausgehend vom Modell wurden schriftliche Testinstrumente und videografierte Lehr-Lern-Rollenspiele entwickelt und bei Physik-Lehramtsstudierenden eingesetzt. Die Ergebnisse sprechen für die Validität der genutzten Testverfahren. (DIPF/Orig.)